Landes to fela: Geography, topography and place in the Battle of Maldon - Thomas, D (Routledge, 2017)
Modern readers of The Battle of Maldon are often confronted in editions and anthologies with explanatory notes or even maps connecting the events of the poem to the present-day topography of Northey Island, in the Blackwater estuary near Maldon, Essex. The presence of such critical apparatus makes tacit or overt claims regarding the poem’s status as a witness to the historical battle fought in August 991. Yet the identification of Northey Island as either the location of the battle, or the location described by the poet, remains unproven. A too-ready acceptance of this hypothetical identification has unduly influenced the study of the poem, discouraging investigation into the poetic significance of the topography of the battlefield. In fact, the construction of a sense of local place is central to the poet’s technique, relating the threat posed by the Viking forces to contemporary concerns about landownership in the late Anglo-Saxon period.